HARD SKILLS, INTRINSIC MOTIVATION, AND CAREER DEVELOPMENT ON EMPLOYEE PERFORMANCE - M. Imam Muttaqijn; Dwi Putra Muhammad Dhiya Hibatullah (Universitas Muhammadiyah Tangerang, 2026)
Purpose – This study examines the influence of hard skills, intrinsic motivation, and career development on employee performance at Point Coffee Tangerang 1. Methodology – A quantitative approach with a descriptive survey design was employed. The population comprised 121 employees, with a sample of 93 respondents. Data were collected through structured questionnaires using a 5-point Likert scale. Instrument validation included content validity assessment and reliability testing. Data analysis encompassed descriptive statistics, classical assumption tests, multiple linear regression, and hypothesis testing. Findings – The results demonstrate that hard skills, intrinsic motivation, and career development each exert a positive and significant effect on employee performance. Simultaneously, the three variables significantly influence employee performance, collectively explaining a substantial proportion of the variance. The findings confirm that technical competence, internal drive, and career advancement opportunities are critical determinants of workforce productivity. Originality – This study contributes to the human resource management literature by examining these variables within the Indonesian coffee shop context, extending Human Capital Theory, Self-Determination Theory, and Career Development Theory to the hospitality sector.